2016
DOI: 10.1103/physrevd.93.045031
|View full text |Cite|
|
Sign up to set email alerts
|

Spin precession of slow neutrons in Einstein-Cartan gravity with torsion, chameleon, and magnetic field

Abstract: We analyse a spin precession of slow neutrons in the Einstein-Cartan gravity with torsion, chameleon and magnetic field. For the derivation of the Heisenberg equation of motion of the neutron spin we use the effective low-energy potential, derived by Ivanov and Wellenzohn (Phys. Rev. D 92, 125004 (2015)) for slow neutrons, coupled to gravitational, chameleon and torsion fields to order 1/m, where m is the neutron mass. In addition to this low-energy interactions we switch on the interaction of slow neutrons w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…These results are consistent with the alternative empirical estimates for the torsion limits [29][30][31][32][33][34][35][36][37][38]. As another powerful tool one can mention the use of the quantum interferometry to probe the spacetime structure, including the search for possible post-Riemannian deviations, focusing on the detection of the phase shift and polarization rotation effects for the neutron and atom beams [55][56][57][58][59].…”
Section: Experimental Manifestations Of Spin-torsion Couplingsupporting
confidence: 83%
See 3 more Smart Citations
“…These results are consistent with the alternative empirical estimates for the torsion limits [29][30][31][32][33][34][35][36][37][38]. As another powerful tool one can mention the use of the quantum interferometry to probe the spacetime structure, including the search for possible post-Riemannian deviations, focusing on the detection of the phase shift and polarization rotation effects for the neutron and atom beams [55][56][57][58][59].…”
Section: Experimental Manifestations Of Spin-torsion Couplingsupporting
confidence: 83%
“…Experimental search for the nontrivial torsion effects is naturally embedded into the broader framework of the studies of the spin-dependent long-range forces [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. By making use of the corresponding experimental techniques, it is possible to find strong limits on the values of the gauge gravity spin-torsion coupling constants and on the torsion field itself.…”
Section: Experimental Manifestations Of Spin-torsion Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of torsion in the framework of Einstein-Cartan theory in early-Universe cosmology were investigated in [21], while the gravitational collapse of a homogeneous Weyssenhoff fluid sphere, in the presence of a negative cosmological constant, was considered in [22]. For recent investigations of the cosmology and astrophysics of Einstein-Cartan theory see [23][24][25][26][27][28][29][30][31][32]. In [33] it was shown that by enlarging the EinsteinCartan Lagrangian with suitable kinetic terms quadratic in the gravitational gauge field strengths (torsion and curvature) one can obtain some new, massive propagating gravitational degrees of freedom.…”
mentioning
confidence: 99%